PASAR MODERN DAN REPITALISASI PASAR TRADISIONAL DI DENPASAR - I Wayan Adnyana; Ni Nyoman Murniasih; I Dewa Putu Juwana; Ni Luh Putu Yesy Anggreni; Putu Siti Firmani (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
This study investigation on how the organization of the modern retail business and traditional market revitalization. It was conducted in Denpasar. A type of data collected in this research in qualitative data supported by quantitative data as complement to its support. Qualitative data was obtained from a variety of information, from the respondents and from observation activities being conducted. While the quantitative data was in the form of statistical records found at the research site. Respondents in this study were the modern retail business and small traders in traditional market. This research emphasized on two types of data collection techniques, namely (1) participation observation and (2) In-depth interviews. The data in the present study were analyzed descriptively, qualitatively and interpretatively. The head to head competition, as a consequence of the fast growth of modern market, badly affected the existence of the traditional market. The existence of the modrn market among the traditional market caused the traders and their omzet to decrease.